The Upregulation of Anti-apoptotic BIRC3 Expression Facilitates Zika Virus Infection - Pandeya, Anup; Songprakhon, Pucharee; Ruangsawat, Punnada; Malakar, Shilu; Noisakran, Sansanee; Morchang, Atthapan; Uiprasertkul, Mongkol; Phatihattakorn, Chayawat; Auewarakul, Prasert; Yenchitsomanus, Pa-thai; Limjindaporn, Thawornchai (Siriraj Medical Journal, 2026)
Objective: The aim of this study was to investigate the apoptotic gene expression profile and to identify the genes involved in apoptosis and ZIKV infection. Materials and Methods: SH-SY5Y cell line was infected with ZIKV at an MOI of 5. The cells were stained with Annexin V and propidium iodide to determine apoptosis. A real-time polymerase chain reaction array was employed to determine the apoptotic gene expression profile in a ZIKV-infected SH-SY5Y cell line. Western blot analysis was performed to confirm the expression of BIRC3 in both SH-SY5Y and A549 cell lines. Knockdown of the BIRC3 was done in ZIKV-infected A549 cell line using BIRC3 -specific siRNA. The ZIKV production was measured by focus-forming unit assay. Results: Apoptotic genes in both extrinsic and intrinsic pathways, such as TNF-α, TRAIL, FAS, CASP8, CASP9, and BIRC3, were found to be upregulated. The anti-apoptotic gene BIRC3 was selected and found to be upregulated at the protein level in both ZIKV-infected SH-SY5Y and ZIKV-infected A549 cell lines. Knockdown of the BIRC3 gene in ZIKV-infected A549 cell line decreased Zika virus NS1 protein expression and Zika virion production. Conclusion: The upregulation of anti-apoptotic BIRC3 expression facilitates Zika virus infection.